EFFECTS OF REACTION FORCES GENERATED BY MANDIBULAR MOVEMENTS ON THE STRUCTURES OF THE JAW - A FINITE ELEMENT METHOD STUDY - Veronica Mercuț; Răzvan Mercuț; Horia Octavian Manolea; Adina Turcu; Petre Mărășescu; Mihaela Vătu; Monica Scrieciu; Laurențiu Dragoș Popa; Vladutu Diana Elena; Sanda Mihaela Popescu (Romanian Society of Oral Rehabilitation, 2021)
Introduction: The aim of the study was to highlight the effects of the reaction forces that produce stress on the hard structures of the jaw during mandibular lateral movement by using the finite element method. For a good understanding of the distribution and intensity of these forces during lateral movement, two clinical models from which the virtual models were obtained were studied. The first model was with advanced wear and end to end occlusion and the other was with bruxism and Angle Class II 2 with deep overbite. These two models were compared with an ideal virtual masticatory system. Materials and Methods: The study used a virtual masticatory system model obtained in a previous study which was considered to be ideal. This model was used to obtain the two virtual models based on the dental casts of the two real clinical cases. Results: The maximum load measured by stress, displacement and strain was recorded in the deep overbite patient model, followed by the end to end occlusion patient model and then the ideal model. Loading, represented by stress, displacement, and strain, was localized on compact bone tissue of the jaw: canine eminence, sutures of the viscerocranium, and even in the palatine bone. In the mandible, maximum load localization represented by stress, displacement and strain was on the compact bone in the premolar region and mandibular symphysis. Conclusions: The study demonstrated the presence of stress generated by the reaction forces and its distribution to the jaw bone during mandibular movement. The highest stress value was recorded in the case of deep overbite patient, suggesting that the mandible has the greatest deformation in lateral movement in the occlusion.